The use of antihistamines in children. Issue 7 (July 2016) - Anagnostou, Katherine; Swan, Kate E.; Brough, Helen
Abstract: Antihistamines are commonly used in paediatric medicine mainly for the treatment of allergic conditions. First generation antihistamines have been in use for many years, despite limited research studies supporting their use. Second generation antihistamines have been investigated for both efficacy and safety in paediatrics. An optimal understanding of their effects and pharmacology are required for optimal use in each patient. In this review we discuss the indications for use, as well as efficacy and safety of both old and newer antihistamines for the paediatric population.